Operational Excellence and the Implications for Health, Safety and Environmental Performance in the Oil and Gas Industry - Muazu, Muazu Hassan (Journal of Technology Management and Business, 2019)
The rise in the cost of production, health, safety and environmental issues are some of the daring challenges faced by the oil sector in recent time. This article is aimed at reviewing literature (reports, articles and theses) and antecedents of research in operational excellence and related field in order to understand the actual problems and their root causes. The performance of the Nigerian National Petroleum Corporation (NNPC)’s refineries, health and safety, the environment and revenue generation was also discussed. The findings indicated that although operational excellence was adopted, the health, safety and environmental (HSE) performance has been falling down, as incidents and fatalities issues are rising. Oil spillage and gas flaring are no way near stopping, outdated regulations, increasing unplanned plant shutdown, refineries performing below capacity and production deferments. The paper thus concludes that the Nigerian oil sector, particularly the NNPC should imbibe risk management culture and training, deploy dynamic technologies, employ enterprise-wide risk management strategy and upgrade the entire regulatory framework governing oil and gas activities.